Monossomia do cromossomo E3 em felinos FeLV positivos com neoplasias hematopoiéticas - Centenaro, Vanessa Bridi (2017)
Hematopoietic tumors are the most common neoplastic disorders in felines. Many of these tumors are associated with infection by feline leukemia virus (FeLV) and one of the described mechanisms is the integration of viral material into the feline genome, which can lead to genomic instability and consequent alteration of genes related to proliferation control and cell death. When larger DNA fragments are affected, such changes can be observed by cytogenetic analysis. The present study aimed to observe cytogenetic changes in felines with hematopoietic neoplasms. The study was performed in eight felines, seven of them with a diagnosis of leukemia or lymphoma. The control consisted of a healthy feline FeLV negative with normal karyotype. At least 10 metaphases of each animal were analyzed. Additionally, 1000 lymphocytes of these two patients, were analyzed and classified cytologically by their viability (necrosis, apoptosis), mitotic state (mononuclear, binucleate (BN), mitotic multinucleate) and their chromosomal damage or instability state (presence of micronucleus (MN) in mononuclear, binucleate, as well as nuclear buds (NBUD). The results of this observation were statistically analyzed by the Wilcoxon paired test. In this chromosomal analysis two of these animals presented monosomy of the E3 chromosome, one with diagnosis of acute myeloid leukemia of the M6a (LMA-M6a) FAB subtype and another with multicenter lymphoma (LM). There were significant differences in LMA-M6a scores (N = 7, Z = 2.36, p = 0.01) and LM scores (N = 8, Z = 2.52, p = 0.01) when group control. However, there was no difference between AML and lymphoma (N = 8, Z = 0.07, p = 0.94). The E3 chromosome has 1401 genes, several related to cell cycle control (Plk1, Sun, Mad1l1, Mcm7), DNA repair (Pms2, Usp42), tumor suppression (Bcl7b). The loss of DNA fragments, such as the loss of the E3 chromosome in the two patients described, led to the haploinsufficiency of important genes for the cell cycle, and this could be a cause of genomic instability and consequently susceptibility to the development of cancer. The observation of cytogenetic alterations, in this way, allows a better understanding of the cancer in the feline species and translational research.